Negative pole piece, electrochemical device and electronic equipment
By layering the mixed coating of graphite and Si-containing coating on the negative electrode current collector surface of the lithium-ion battery, the control of nano-indentation test can restore displacement, solving the problem of volume expansion during the cycle of Si negative electrode material, and achieving the effect of reducing battery expansion while maintaining energy density.
Patent Information
- Application Number
- CN202480004530.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-15
- Publication Date
- 2025-06-20
AI Technical Summary
The volume expansion and contraction of Si negative electrode materials in lithium-ion batteries during circulation leads to huge expansion of the battery, limiting the application of Si negative electrodes in lithium batteries.
By layering the mixed coating of graphite and Si-containing coating on the negative electrode current collector surface, the nanoindentation test of the second film layer can be restored to the range of 60% to 100% to reduce expansion of the battery cycle process.
Without reducing the energy density of the electrochemical device, the volume expansion during the battery cycle is effectively reduced, and the cycle life and dynamic performance of the battery are improved.
Smart Images

Figure CN120188281A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to a negative electrode sheet, an electrochemical device, and an electronic device. Background Art
[0002] Due to its advantages such as high energy density, high working voltage, good load characteristics, and fast charging speed, lithium-ion batteries have been rapidly and widely applied in fields such as mobile phones, micro cameras, palmtop computers, and laptop computers.
[0003] However, with the continuous improvement of the requirements for battery energy and power performance in downstream applications, higher requirements are also put forward for the cycle performance of lithium-ion batteries. Summary of the Invention
[0004] The energy density of the graphite negative electrode of traditional lithium batteries has approached the theoretical limit. As the most promising material to replace graphite, Si has the advantages of low cost, easy availability of raw materials, and high energy density.
[0005] At the same time, the biggest challenge in the application of Si negative electrodes is the volume expansion and contraction of more than 300% during the lithium insertion and extraction process of Si particles, which will cause huge expansion of the battery, resulting in ED loss after cycling, and restricting the application of Si negative electrodes in lithium batteries.
[0006] Based on the above considerations, the purpose of the present application is to provide an electrochemical device and an electronic device; without reducing the energy density of the electrochemical device, the volume expansion of the battery during cycling is reduced.
[0007] The embodiments of the present application are implemented as follows:
[0008] In a first aspect, an embodiment of the present application provides a negative electrode sheet, which includes: a negative electrode current collector, a first film layer, and a second film layer. The first film layer includes a first negative electrode active material, and the first negative electrode active material is graphite. The second film layer includes a second negative electrode active material, and the second negative electrode active material includes a silicon-carbon material. Relative to the second film layer, the first film layer is formed as a layer close to the surface of the negative electrode current collector. The nanoindentation test of the second film layer satisfies: the recoverable displacement is 60% to 100%.
[0009] When applying Si to a lithium-ion battery, a mixed coating of Si and graphite can be coated on the surface of the negative electrode current collector. However, the inventor found that when Si and graphite are completely mixed and directly applied to a lithium-ion battery, the Si expansion will cause an immediate increase in the expansion of the electrode sheet, which is immediately reflected in the increase in the thickness of the battery.
[0010] Through research, coating the graphite layer and the Si-containing layer on the surface of the negative electrode current collector in layers is beneficial to improving the increase in battery thickness caused by Si expansion. Through further research, by controlling the recoverable displacement of the nanoindentation test of the second film layer within a certain range, it is possible to reduce the expansion during battery cycling while taking into account not reducing the energy density of the battery.
[0011] In the above technical solution, by controlling the recoverable displacement of the second film layer to be 60% - 100%, it is possible to reduce the expansion during battery cycling while taking into account not reducing the energy density of the battery.
[0012] In some alternative embodiments, for the above negative electrode sheet, the recoverable displacement is 80% - 100%.
[0013] In the above technical solution, by further restricting the nanoindentation test of the second film layer to meet: the recoverable displacement is 80% - 100%, it is possible to further reduce the expansion during battery cycling while taking into account not reducing the energy density of the battery.
[0014] In some alternative embodiments, for the above negative electrode sheet, the mass percentage content of Si element in the second film layer is 10% ≤ W1 ≤ 25%; the second film layer includes: a binder; the binder includes: at least one of polyurethane, polyimide, and polyamideimide; calculated by mass percentage of the second film layer, the second film layer includes: 2% - 12% binder.
[0015] In the above technical solution, polyurethane, polyimide, and polyamideimide binders are high-toughness binders; the characteristic element of such binders is N, which forms hydrogen bonds and covalent bonds with Si-OH on the surface of Si in the negative electrode sheet, improving the bonding strength and toughness of the negative electrode sheet; it is beneficial to improving the resilience performance of the negative electrode sheet after compression.
[0016] In some alternative embodiments, calculated by mass percentage of the second film layer, the mass percentage content of Si element in the second film layer is W1; 15% ≤ W1 ≤ 25%; the second film layer includes: 6% - 10% binder. In some alternative embodiments, for the above negative electrode sheet, the coating weight ratio of the second film layer to the first film layer is 0.10 - 0.50.
[0017] In the above technical solution, by controlling the coating weight ratio of the second film layer to the first film layer within the above range, it is further beneficial to reduce the expansion during battery cycling while taking into account not reducing the energy density of the battery.
[0018] In some alternative embodiments, the coating weight ratio of the second film layer to the first film layer is 0.10 - 0.20.
[0019] In some alternative embodiments, for the above-mentioned negative electrode sheet, the D n 10 of the silicon-carbon material is 3.7 μm to 5.0 μm.
[0020] The D n 10 of the silicon-carbon material can reflect the content of the small particle (or fine powder) part in the material particles. Generally, the smaller the D n 10, the better the electronic conductivity of the negative electrode sheet, the higher the content of the small particle (or fine powder) part in the negative electrode film, and the higher the probability of blockage of the pore channels of the negative electrode porous electrode, which is not conducive to the ion conduction of the negative electrode sheet; the probability of side reactions will also increase. Through research, when the D n 10 is controlled to be 3.7 μm to 5.0 μm, both the electronic conductivity and the ion conductivity of the overall negative electrode sheet can be maintained at an excellent level. The negative electrode sheet has a small charge transfer resistance and a high electro-chemical reaction rate. The negative electrode sheet can have excellent kinetic performance, which is beneficial to reducing the swelling during the battery cycle while taking into account not reducing the energy density of the battery.
[0021] In some alternative embodiments, the D n 10 of the silicon-carbon material is 3.7 μm to 4.0 μm.
[0022] In some alternative embodiments, for the above-mentioned negative electrode sheet, the D v 10 of the silicon-carbon material is 5.1 μm to 6.1 μm.
[0023] The D v 10 represents the particle size corresponding to when the cumulative volume distribution percentage of the material reaches 10%. The silicon-carbon material with too small a particle size will increase the side reaction between the silicon-carbon and the electrolyte, and the increase in by-products will deteriorate the cycle swelling; too large a particle size will deteriorate the material kinetics, and the cycle lithium deposition will lead to the deterioration of the cycle swelling. Therefore, it is necessary to control not only Dn10, but also D v 10.
[0024] In the above technical solution, by further controlling the D v 10 of the silicon-carbon material within the above range, it can cooperate synergistically with the D n 10 of the silicon-carbon material being 3.4 μm to 5.0 μm; the D V 10 can control the proportion of small particles in the overall active material, and the D n 10 further controls the number of smaller particle sizes on the basis of the D v 10 requirement, which plays a role in reducing the side reaction between the material and the electrolyte, and is beneficial to reducing the swelling during the battery cycle while taking into account not reducing the energy density of the battery.
[0025] In some alternative embodiments, for the above-mentioned negative electrode sheet, the D v 50 of the silicon-carbon material is 8.3 μm to 10.3 μm.
[0026] In the above technical solution, by controlling D of the silicon-carbon material v 50 within the above range, it is further beneficial to reduce the swelling during battery cycling while taking into account not reducing the energy density of the battery.
[0027] In some alternative embodiments, for the above negative electrode sheet, the silicon-carbon material satisfies at least one of the following characteristics:
[0028] (1) D of the silicon-carbon material v 90 is 13.5 μm to 16.5 μm;
[0029] (2) D of the silicon-carbon material v 99 is less than or equal to 25.0 μm;
[0030] (3) The specific surface area of the silicon-carbon material is 1.00 m 2 / g to 3.50 m 2 / g;
[0031] (4) The tap density of the silicon-carbon material is 0.85 g / cm 3 to 1.05 g / cm 3 .
[0032] In a second aspect, an embodiment of the present application provides an electrochemical device, which includes: the negative electrode sheet provided in the first aspect above.
[0033] In a third aspect, an embodiment of the present application provides an electronic device, which includes the electrochemical device provided in the second aspect above. Description of the Drawings
[0035] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the following will briefly introduce the drawings required for the embodiments. It should be understood that the following drawings only show some embodiments of the present application, and therefore should not be regarded as limiting the scope. For those of ordinary skill in the art, without creative efforts, other related drawings can also be obtained based on these drawings.
[0036] Figure 1 Schematically shows the structure diagram of the negative electrode sheet;
[0037] Figure 2 Schematically shows the nanoindentation test relationship diagram.
[0038] Icon:
[0039] Negative electrode sheet 100; negative electrode current collector 101; first film layer 110; second film layer 120. Detailed Description of the Embodiments
[0041] The embodiments of the technical solution of the present application will be described in detail below with reference to the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present application, so they are only examples and cannot be used to limit the protection scope of the present application.
[0042] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by those of ordinary skill in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" and any variations thereof in the specification and claims of this application and the above description of the drawings are intended to cover non-exclusive inclusion.
[0043] In the description of the embodiments of the present application, technical terms such as "first" and "second" are only used to distinguish different objects and cannot be understood as indicating or implying relative importance or implicitly indicating the quantity, specific order or primary-secondary relationship of the indicated technical features.
[0044] Reference to "embodiment" herein means that a particular feature, structure or characteristic described in connection with the embodiment can be included in at least one embodiment of the present application. The phrase appears in various places in the specification and does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment mutually exclusive with other embodiments. Those skilled in the art will explicitly and implicitly understand that the embodiments described herein can be combined with other embodiments.
[0045] In the embodiments of the present application, the same reference numerals represent the same components, and for the sake of brevity, the detailed description of the same components is omitted in different embodiments. It should be understood that the heights, lengths, widths and other dimensions of various components shown in the accompanying drawings in the embodiments of the present application, as well as the overall height, length, width and other dimensions of the integrated device are only for illustrative purposes and should not constitute any limitation to the present application.
[0046] Referring to Figure 1 , some embodiments of the present application provide a negative electrode plate 100, and the negative electrode plate 100 includes:
[0047] A negative electrode current collector 101;
[0048] A first film layer 110, the first film layer 110 includes a first negative electrode active material, and the first negative electrode active material is graphite; and
[0049] A second film layer 120; the second film layer 120 includes a second negative electrode active material, and the second negative electrode active material includes a silicon-carbon material; relative to the second film layer 120, the first film layer 110 is close to the surface of the negative electrode current collector 101;
[0050] The nanoindentation test of the second film layer satisfies that the recoverable displacement is 60% to 100%.
[0051] In the above technical solution, the nano-indentation test of the second film layer satisfies: the recoverable displacement is 60% - 100%; it can reduce the growth of porosity to reduce the expansion of the negative electrode, which is beneficial to the integrity of the conductive network during the battery cycle and beneficial to the battery cycle life. At the same time, the above technical solution can take into account not reducing the energy density of the battery.
[0052] In some embodiments of the present application, the nano-indentation test of the second film layer satisfies: the recoverable displacement S1 / S2 is 60%, 65%, 72%, 75%, 78%, 80%, 82%, 85%, 88%, 90%, 92%, 95%, 98%, 100% or the range between any two of the foregoing values.
[0053] In some embodiments of the present application, the nano-indentation of the above-mentioned second film layer can represent the resilience performance after compression of the second film layer. When the negative electrode sheet is assembled into a battery, the negative electrode sheet is subjected to a downward pressure, and the second film layer (including the Si layer) can rebound after being pressed down, which can reduce the growth of porosity to reduce the expansion of the negative electrode.
[0054] In some embodiments of the present application, the above-mentioned recoverable displacement S1 / S2 is 80% - 100%.
[0055] In the above technical solution, by setting the mass percentage content W1 of the Si element in the second film layer within the above range, and further restricting the nano-indentation test of the second film layer to satisfy: the recoverable displacement S1 / S2 is 80% - 100%; it can further reduce the expansion during the battery cycle while taking into account not reducing the energy density of the battery.
[0056] Exemplarily, in some embodiments of the present application, the above-mentioned recoverable displacement S1 / S2 is 80%, 81%, 82%, 85%, 88%, 90%, 92%, 95%, 98%, 99%, 100% or the range between any two of the foregoing values.
[0057] In some embodiments of the present application, the mass percentage content of Si element in the second film layer 120 is W1, measured by the mass percentage of the second film layer; 10%≤W1≤25%; illustratively, the mass percentage content of Si element in the second film layer 120 is 10%, 11%, 12%, 14%, 15%, 16%, 18%, 20%, 22%, 24%, 25% or the range between any two of the above values, measured by the mass percentage of the second film layer; the second film layer includes: a binder; the binder includes: at least one of polyurethane, polyimide, and polyamide-imide; measured by the mass percentage of the second film layer, the second film layer includes: 2% to 12% binder. Exemplarily, measured by mass percentage, the second film layer includes: 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12% or the range between any two of the above values.
[0058] In the above technical solution, the second film layer includes, in terms of the mass percentage of the second film layer: 2.5% to 10% binder; which can cooperate with the mass percentage content of the Si element in the second film layer (10% ≤ Si% ≤ 25%) to produce a synergistic effect, effectively improve the rebound performance of the negative electrode plate after compression, reduce the growth of porosity to reduce the expansion of the negative electrode, improve the integrity of the conductive network during the cycle process, and maintain a better cycle life; thereby achieving the goal of reducing the expansion of the battery during the cycle process while not reducing the energy density of the battery.
[0059] In some embodiments of the present application, the mass percentage content of Si element in the second film layer is W1, measured by mass percentage of the second film layer; 15%≤W1≤25%; the second film layer includes: 6% to 10% binder.
[0060] Within the above range, the mass percentage content of Si element in the second film layer is W1; 15%≤W1≤25%; the second film layer includes: 6% to 10% binder; which is more conducive to reducing the expansion of the battery during the cycle while not reducing the energy density of the battery.
[0061] Exemplarily, in terms of the mass percentage of the second film layer, the mass percentage content of Si element in the second film layer is W1; 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25% or a range between any two of the foregoing values; the second film layer includes: 6%, 7%, 8%, 9%, 10% or a range between any two of the foregoing values of a binder. In some embodiments, the second film layer further includes a conductive agent and a thickener.
[0062] In some embodiments of the present application, the second film layer includes, by weight percentage, 85% to 97.5% silicon-carbon material, 2% to 12% binder, 0.25% to 2% conductive agent, and 0.25% to 1% thickener.
[0063] In some embodiments of the present application, the conductive agent includes, but is not limited to: carbon-based materials, metal-based materials, conductive polymers and mixtures thereof. In some embodiments, the carbon-based material is selected from carbon nanotubes, natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, or carbon fiber and any combination thereof. In some embodiments, the metal-based material is selected from metal powder, metal fiber, copper, nickel, aluminum or silver. In some embodiments, the conductive polymer is a polyphenylene derivative.
[0064] In some embodiments of the present application, the thickener includes, but is not limited to, at least one of sodium carboxymethyl cellulose, potassium carboxymethyl cellulose, sodium hydroxymethyl cellulose, and potassium hydroxymethyl cellulose.
[0065] In some embodiments of the present application, the second film layer includes, by mass percentage: 17% to 50% silicon-carbon material, 35% to 80% graphite, 2% to 12% polyurethane, 0.25% to 2% carbon nanotubes, and 0.25% to 1% sodium carboxymethyl cellulose.
[0066] In some embodiments of the present application, the ratio of the coating weight of the second film layer to the coating weight of the first film layer is 0.10 to 0.50.
[0067] In some embodiments of the present application, illustratively, the ratio of the coating weight of the second film layer to the coating weight of the first film layer is 0.10, 0.20, 0.30, 0.40, 0.50 or a range between any two of the foregoing values.
[0068] In the above technical solution, by controlling the ratio of the coating weight of the second film layer to the coating weight of the first film layer within the above range, it is further beneficial to reduce the expansion of the battery during the cycle while not reducing the energy density of the battery.
[0069] In some embodiments of the present application, the ratio of the coating weight of the second film layer to the coating weight of the first film layer is 0.10 to 0.20.
[0070] Illustratively, the ratio of the coating weight of the second film layer to the coating weight of the first film layer is 0.10, 0.11, 0.12, 0.13, 0.14, 0.15, 0.16, 0.17, 0.18, 0.19, 0.20, or a range between any two of the foregoing values.
[0071] In some embodiments of the present application, D of the silicon-carbon material nThe D10 is from 3.7 μm to 5.0 μm.
[0072] In some embodiments of the present application, by way of example, the D n 10 of the silicon-carbon material is 3.7 μm, 3.8 μm, 3.9 μm, 4.0 μm, 4.1 μm, 4.2 μm, 4.3 μm, 4.4 μm, 4.5 μm, 4.6 μm, 4.7 μm, 4.8 μm, 4.9 μm, 5.0 μm or the range between any two of the foregoing values. The D n 10 of the silicon-carbon material is within the above range, and the negative electrode sheet can have excellent kinetic performance, which is beneficial to taking into account not reducing the energy density of the battery while reducing the swelling during the battery cycle.
[0073] In some embodiments of the present application, the Dn10 of the silicon-carbon material is from 3.7 μm to 4.0 μm.
[0074] In some embodiments of the present application, the D v 10 of the silicon-carbon material is from 5.1 μm to 6.1 μm.
[0075] In some embodiments of the present application, by way of example, the D v 10 of the silicon-carbon material is 5.1 μm, 5.2 μm, 5.3 μm, 5.4 μm, 5.5 μm, 5.6 μm, 5.7 μm, 5.8 μm, 5.9 μm, 6.0 μm, 6.1 μm or the range between any two of the foregoing values.
[0076] In some embodiments of the present application, the D v 50 of the silicon-carbon material is from 8.3 μm to 10.3 μm.
[0077] In some embodiments of the present application, by way of example, the D v 50 of the silicon-carbon material is 8.3 μm, 8.4 μm, 8.5 μm, 8.6 μm, 8.7 μm, 8.8 μm, 8.9 μm, 9.0 μm, 9.1 μm, 9.2 μm, 9.3 μm, 9.4 μm, 9.5 μm, 9.6 μm, 9.7 μm, 9.8 μm, 9.9 μm, 10.0 μm, 10.1 μm, 10.2 μm, 10.3 μm or the range between any two of the foregoing values.
[0078] In the above technical solutions, by controlling the D v 50 of the silicon-carbon material within the above range, it is further beneficial to taking into account not reducing the energy density of the battery while reducing the swelling during the battery cycle.
[0079] In some embodiments of the present application, the silicon-carbon material satisfies at least one of the following characteristics:
[0080] (1) D of the silicon-carbon material v 90 is 13.5 μm to 16.5 μm;
[0081] (2) D of the silicon-carbon material v 99 is less than or equal to 25.0 μm;
[0082] (3) The specific surface area of the silicon-carbon material is 1.00 m 2 / g to 3.50 m 2 / g;
[0083] (4) The tapped density of the silicon-carbon material is 0.85 g / cm 3 to 1.05 g / cm 3 .
[0084] Exemplarily, in some embodiments of the present application, D of the silicon-carbon material v 90 is 13.5 μm, 13.8 μm, 14.0 μm, 14.2 μm, 14.5 μm, 15.0 μm, 15.5 μm, 16.0 μm, 16.1 μm, 16.2 μm, 16.3 μm, 16.4 μm, 16.5 μm or the range between any two of the foregoing values.
[0085] Exemplarily, in some embodiments of the present application, D of the silicon-carbon material v 99 is 25.0 μm, 20.0 μm, 15.0 μm, 10.0 μm or the range between any two of the foregoing values.
[0086] Exemplarily, in some embodiments of the present application, the specific surface area of the silicon-carbon material is 1.00 m 2 / g, 1.05 m 2 / g, 1.10 m 2 / g, 1.20 m 2 / g, 1.30 m 2 / g, 1.40 m 2 / g, 1.50 m 2 / g, 2.50 m 2 / g, 2.80 m 2 / g, 3.00 m 2 / g, 3.50 m 2 / g or the range between any two of the foregoing values.
[0087] Exemplarily, in some embodiments of the present application, the tapped density of the silicon-carbon material is 0.85 g / cm 3 , 0.86 g / cm 3 , 0.87 g / cm 3 , 0.88 g / cm 3 , 0.89 g / cm3 , 0.90 g / cm 3 , 0.92 g / cm 3 , 0.95 g / cm 3 , 0.98 g / cm 3 , 1.0 g / cm 3 , 1.01 g / cm 3 , 1.02 g / cm 3 , 1.03 g / cm 3 , 1.04 g / cm 3 , 1.05 g / cm 3 or the range between any two of the aforementioned values.
[0088] In this application, the volume distribution particle sizes D v 10, D v 50, D v 90, D v 99 have meanings well-known in the art, which respectively represent the particle sizes corresponding to when the cumulative volume distribution percentage of the material reaches 10%, 50%, 90%, and 99%, and can be measured by instruments and methods known in the art. For example, it can be measured by referring to GB / T 19077-2016 and using a laser particle size analyzer. The test instrument can be the Mastersizer 3000 type laser particle size analyzer of Malvern Instruments Limited, UK.
[0089] In this application, the number distribution particle size D n 10 has a meaning well-known in the art, which represents the particle size corresponding to when the cumulative number distribution percentage of the material reaches 10%, and can be measured by instruments and methods known in the art. For example, it can be measured by referring to GB / T 19077-2016 and using a laser particle size analyzer. The test instrument can be the Mastersizer 3000 type laser particle size analyzer of Malvern Instruments Limited, UK.
[0090] In this application, the specific surface area of the material has a meaning well-known in the art and can be measured by instruments and methods known in the art. For example, it can be tested by referring to GB / T 19587-2017 using the nitrogen adsorption specific surface area analysis test method and calculated by the BET (Brunauer Emmett Teller) method. The test instrument can be the Tri-Star 3020 type specific surface area and pore size analyzer of Micromeritics, USA.
[0091] In this application, the tapped density of the material has a meaning well-known in the art and can be measured using instruments and methods known in the art. For example, reference can be made to GB / T 5162-2006 and a powder tapped density tester can be used for measurement. The test instrument can be BT-301 from Dandong BETTER, and the test parameters are as follows: vibration frequency 250 ± 15 times / minute, amplitude 3 ± 0.2 mm, number of vibrations 5000 times, graduated cylinder 25 mL.
[0092] In some embodiments of this application, the initial discharge specific capacity of the above-mentioned silicon-carbon material is 1675.0 mAh / g to 1775.0 mAh / g.
[0093] Exemplarily, in some embodiments of this application, the initial discharge specific capacity of the above-mentioned silicon-carbon material is 1675.0 mAh / g, 1685.0 mAh / g, 1695.0 mAh / g, 1700.0 mAh / g, 1750.0 mAh / g, 1770.0 mAh / g, 1775.0 mAh / g or the range between any two of the foregoing values.
[0094] In this application, the specific capacity of the material (such as the silicon-carbon material) has a meaning well-known in the art and can be tested using methods known in the art. An exemplary test method is as follows: Mix the silicon-carbon material sample powder with conductive agent carbon black (Super P) and binder polyvinylidene fluoride (PVDF) in a mass ratio of 91.6:1.8:6.6 with solvent N-methylpyrrolidone (NMP) to make a slurry; coat the prepared slurry on the surface of the negative current collector copper foil and dry it in an oven for later use; Mix ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) in a volume ratio of 1:1:1 to obtain an organic solvent, and then dissolve LiPF6 in the above organic solvent to prepare an electrolyte with a concentration of 1 mol / L; Then, using a lithium metal sheet as the counter electrode and a polyethylene (PE) film as the separator, assemble a CR2430 type coin cell with the above electrolyte in a glove box under argon protection; After standing the obtained coin cell for 12 h, at 25 °C, perform a constant current discharge at 0.05C to 0.005V, stand for 10 minutes, perform a constant current discharge at 50 μA to 0.005V, stand for 10 minutes, and perform a constant current discharge at 10 μA to 0.005V, and record the discharge capacity. The ratio of the discharge capacity to the sample mass is the initial discharge specific capacity of the corresponding silicon-carbon material.
[0095] In some embodiments of this application, the initial Coulombic efficiency of the above-mentioned silicon-carbon material is 80.5% to 84.5%.
[0096] Illustratively, in some embodiments of the present application, the first coulombic efficiency of the silicon-carbon material is 80.5%, 81.0%, 82.0%, 83.0%, 84.0%, 84.5% or a range between any two of the aforementioned values.
[0097] In this application, the first coulombic efficiency of the material is a well-known meaning in the art and can be tested by methods known in the art. An exemplary test method is as follows: silicon-carbon material powder is mixed with conductive agent carbon black (Super P), binder polyvinylidene fluoride (PVDF) in a mass ratio of 91.6:1.8:6.6 and solvent N-methylpyrrolidone (NMP) to form a slurry; the prepared slurry is applied on the surface of the positive electrode current collector aluminum foil, and dried in an oven for use; ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) are mixed in a volume ratio of 1:1:1 to obtain an organic solvent, and then LiPF6 is dissolved in the above organic solvent to prepare an electrolyte with a concentration of 1 mol / L; then a metal sodium sheet is used as a counter electrode, a polyethylene (PE) film is used as an isolation membrane, and the above electrolyte is assembled into a CR2430 button battery in an argon-protected glove box. After the obtained button battery was allowed to stand for 12 hours, the battery was charged at 25°C at a constant current of 0.1C to a voltage of 5V, and then charged at a constant voltage of 5V to a current of 0.02C. After standing for 5 minutes, the battery was discharged at a constant current of 0.1C to a voltage of 3.0V. This is a charge and discharge cycle process; the gram capacity of the first discharge and the first charge were recorded respectively, and the first coulomb efficiency (ICE) = first charge capacity / first discharge capacity × 100%.
[0098] In some embodiments of the present application, the silicon content in the silicon-carbon material is 45% to 55% by mass.
[0099] In the above technical scheme, by setting the silicon content in the silicon-carbon material within the above range, it is beneficial to cooperate with the aforementioned binder, which can effectively improve the rebound performance of the negative electrode plate after compression, reduce the growth of porosity to reduce the expansion of the negative electrode, and improve the integrity of the conductive network during the cycle process to maintain a better cycle life; thereby achieving the goal of reducing the expansion of the battery during the cycle process while not reducing the energy density of the battery.
[0100] For example, in some embodiments of the present application, the silicon content in the silicon-carbon material is 45%, 46%, 47%, 48%, 49%, 50%, 51%, 52%, 53%, 54%, 55% or a range between any two of the foregoing values, in terms of mass percentage. Further optionally, in some embodiments of the present application, the silicon-carbon material is prepared by chemical vapor deposition (CVD).
[0101] Further optionally, in some embodiments of the present application, the above-mentioned silicon-carbon material can be prepared by the following method:
[0102] Put the carbon precursor into the furnace, introduce a mixed gas of silane / argon with a certain volume fraction, deposit for a period of time at a certain temperature, and then the silicon-carbon material can be obtained.
[0103] Further, in some embodiments of the present application, the above-mentioned "carbon precursor" refers to a substance that can form carbon after deposition at a certain temperature in the above-mentioned preparation method.
[0104] Further optionally, in some embodiments of the present application, the above-mentioned carbon precursor includes:
[0105] At least one of glucose, sucrose, fructose, cellulose, acetylene black, asphalt, carbon nanotubes, starch, citric acid, polyacrylic acid or dopamine.
[0106] Exemplarily, in some embodiments of the present application, the above-mentioned carbon precursor is selected from any one of glucose, sucrose, fructose, cellulose, acetylene black, asphalt, carbon nanotubes, starch, citric acid, polyacrylic acid or dopamine; or the above-mentioned carbon precursor is selected from a mixture of glucose, sucrose and fructose; and the two can be mixed in any proportion.
[0107] In other alternative embodiments of the present application, the above-mentioned "silicon-carbon material" can also be prepared by other well-known methods in the art; or the above-mentioned "silicon-carbon material" can also be obtained by purchasing from the market.
[0108] Further, in some embodiments of the present application, the above-mentioned "graphite" includes at least one of natural graphite, artificial graphite or mesophase carbon microspheres.
[0109] Exemplarily, in some embodiments of the present application, the above-mentioned "graphite" is selected from any one of natural graphite, artificial graphite or mesophase carbon microspheres; or in some embodiments of the present application, the above-mentioned "graphite" is selected from a mixture of natural graphite and artificial graphite, and the two can be mixed in any proportion; or in some embodiments of the present application, the above-mentioned "graphite" is selected from a mixture of natural graphite, artificial graphite and mesophase carbon microspheres, and the three can be mixed in any proportion.
[0110] Further optionally, in some embodiments, the first film layer further includes a first binder and a first thickener. The first binder includes, but is not limited to: polyvinylidene fluoride, polyacrylate, polyacrylic acid, polyimide, polyamide, polyamide-imide, styrene-butadiene rubber, sodium alginate, polyvinyl alcohol, polytetrafluoroethylene, polyacrylonitrile; further optionally, the first binder is selected as styrene-butadiene rubber. The first thickener includes but is not limited to at least one of sodium carboxymethyl cellulose, potassium carboxymethyl cellulose, sodium hydroxymethyl cellulose, and potassium hydroxymethyl cellulose.
[0111] Further optionally, in some embodiments of the present application, exemplarily, by mass percentage, the first film layer includes: 97% - 98% graphite; 1.8% - 2.4% first binder; 0.2% - 0.6% first thickener.
[0112] Exemplarily, in some embodiments of the present application, by mass percentage, the first film layer includes: 97% - 98% graphite, 1.8% - 2.4% polyvinylidene fluoride, 0.2% - 0.6% sodium carboxymethyl cellulose.
[0113] Further, in some embodiments of the present application, the above-mentioned negative electrode tab includes a negative electrode current collector. In some embodiments, the negative electrode current collector includes: copper foil, aluminum foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam, a polymer substrate coated with a conductive metal, or any combination thereof.
[0114] Further, the negative electrode tab of the present application can be prepared by well-known methods in the art. Generally, the negative electrode active material (such as graphite and silicon-carbon material in the present application), and optionally a conductive agent (such as carbon black and other carbon materials and metal particles, etc.), a binder (such as SBR), and other optional additives (such as PTC thermistor materials) and other materials are mixed and dispersed in a solvent (such as deionized water), stirred evenly and then uniformly coated on the negative electrode current collector, and dried to obtain the negative electrode tab.
[0115] Further, in some embodiments of the present application, exemplarily, the preparation of the negative electrode tab: the negative electrode active materials (silicon particles and graphite particles) are mixed evenly in a certain mass ratio, then a binder, a conductive agent, water, a dispersant, etc. are added, dispersed and stirred evenly, and then the obtained negative electrode slurry is coated on the current collector and dried, and then cold-pressed to obtain the negative electrode tab.
[0116] Some embodiments of the present application provide an electrochemical device, and the electrochemical device includes the negative electrode tab provided in any of the foregoing embodiments.
[0117] In some embodiments of the present application, the above-mentioned electrochemical device includes, but is not limited to: all kinds of primary batteries, secondary batteries or capacitors.
[0118] Exemplarily, in some embodiments of the present application, the above-mentioned electrochemical device is a lithium secondary battery.
[0119] Further, in some embodiments of the present application, the aforementioned electrochemical device further includes a positive electrode plate.
[0120] Further, in some embodiments of the present application, the positive electrode plate includes a positive electrode current collector and a positive electrode active material layer located on the positive electrode current collector. In some embodiments of the present application, the positive electrode active material includes a positive electrode material capable of absorbing and releasing lithium. The positive electrode materials that release lithium include, but are not limited to, lithium cobaltate, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminate, lithium manganate, lithium iron manganese phosphate, lithium vanadium phosphate, lithium vanadium oxyphosphate, lithium iron phosphate, lithium titanate, and lithium-rich manganese-based materials. In some embodiments of the present application, the current collector may include, but is not limited to: aluminum foil.
[0121] In some embodiments of the present application, the positive electrode active material layer further includes a binder, and optionally includes a conductive material. The binder improves the binding between the positive electrode active material particles and also improves the binding between the positive electrode active material and the current collector.
[0122] In some embodiments of the present application, the binder includes, but is not limited to: polyvinyl alcohol, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, polymers containing ethylene oxide, polyvinylpyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylated styrene-butadiene rubber, epoxy resin, or nylon, etc.
[0123] The positive electrode plate can be prepared by methods well known in the art. For example, the positive electrode plate can be obtained by the following method: mixing the active material, the conductive material, and the binder in a solvent to prepare an active material composition, and coating the active material composition on the current collector. In some embodiments, the solvent may include, but is not limited to: N-methylpyrrolidone. The electrochemical device of the present application has a higher energy density and cycling performance and can meet the application requirements.
[0124] Further, in some embodiments of the present application, the aforementioned electrochemical device further includes a separator.
[0125] Further, in some embodiments of the present application, the separator may include a substrate layer and a surface treatment layer. The substrate layer is a non-woven fabric, a film, or a composite film having a porous structure, and the material of the substrate layer is selected from at least one of polyethylene, polypropylene, polyethylene terephthalate, and polyimide. Specifically, a polypropylene porous film, a polyethylene porous film, a polypropylene non-woven fabric, a polyethylene non-woven fabric, or a polypropylene-polyethylene-polypropylene porous composite film can be selected.
[0126] A surface treatment layer is provided on at least one surface of the base material layer. The surface treatment layer can be a polymer layer, an inorganic layer, or a layer formed by mixing polymers and inorganic substances. The inorganic layer includes inorganic particles and a binder. The inorganic particles are selected from at least one of alumina, silica, magnesia, titanium oxide, hafnium dioxide, tin oxide, cerium dioxide, nickel oxide, zinc oxide, calcium oxide, zirconium oxide, yttrium oxide, silicon carbide, boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide, and barium sulfate. The binder is selected from at least one of polyvinylidene fluoride, copolymer of vinylidene fluoride and hexafluoropropylene, polyamide, polyacrylonitrile, polyacrylate, polyacrylic acid, polyacrylate salt, polyvinylpyrrolidone, polyethylene alkoxide, polymethyl methacrylate, polytetrafluoroethylene, and polyhexafluoropropylene. The polymer layer contains a polymer, and the material of the polymer is selected from at least one of polyamide, polyacrylonitrile, acrylate polymer, polyacrylic acid, polyacrylate salt, polyvinylpyrrolidone, polyethylene alkoxide, polyvinylidene fluoride, and poly(vinylidene fluoride - hexafluoropropylene).
[0127] Further, in some embodiments of the present application, the preparation of the lithium - ion battery includes: stacking the positive electrode sheet, the separator, and the negative electrode sheet in sequence, with the separator in the middle of the positive and negative electrodes to play a role in isolation, and winding to obtain a bare battery core. Placing the bare battery core in an outer package, injecting the prepared electrolyte, and then encapsulating it. After processes such as formation, degassing, and edge cutting, a lithium - ion battery (lithium secondary battery) is obtained.
[0128] Some embodiments of the present application provide an electrical device, which includes the electrochemical device provided in any of the foregoing embodiments.
[0130] The following lists some specific embodiments for better illustration of the present application.
[0131] Example 1
[0132] A lithium - ion battery is provided and prepared according to the following steps:
[0133]
Preparation of the negative electrode sheet
[0134] Graphite is mixed with polyvinylidene fluoride and sodium carboxymethyl cellulose to prepare a first film - layer slurry; by mass percentage, graphite: polyvinylidene fluoride: sodium carboxymethyl cellulose is 97%: 2.4%: 0.6%.
[0135] Silicon - carbon material, graphite are mixed with polyurethane, carbon nanotubes, and sodium carboxymethyl cellulose to prepare a second film - layer slurry; by mass percentage, silicon - carbon material: graphite: polyurethane: carbon nanotubes: sodium carboxymethyl cellulose is 20.0%: 74.0%: 5%: 0.5%: 0.5%.
[0136] The specific performance parameters of the silicon - carbon material are shown in Table 2.
[0137] The Si material content (wt%) of the second film layer = the mass of the silicon-carbon material in the second film layer / the mass of the second film layer = 20%.
[0138] Coating is carried out on the surface of a 6-μm-thick copper foil. The coating method is as follows:
[0139] Coat the first film layer slurry on one surface of the copper foil, with a coating mass of 4.9 mg / cm 3 , and after drying, the first film layer is obtained; then coat the second film layer slurry on the first film layer, with a coating mass of 1.6 mg / cm 3 , and after drying, the second film layer is obtained. Repeat the above process on the other surface of the copper foil, and then cold press to an overall compaction density of 1.74 g / cm 3 . Then laser grooving is carried out on the second film layer, with a groove width of 15 μm, a groove interval width of 47 μm, and a groove depth of 10 μm; the negative electrode plate is obtained.
[0140] The comprehensive Si material content (wt%) = the mass of the silicon-carbon material in the second film layer / (the mass of the first film layer + the mass of the second film layer) = 5%.
[0141]
Electrolyte
[0142] In a dry argon atmosphere glove box, mix the organic solvents ethylene carbonate (EC), propylene carbonate (PC), diethyl carbonate (DEC), and ethyl propionate (EP) in a mass ratio of 3:1:3:3 to obtain a mixed solvent component, and then add the lithium salt LiPF6 to prepare an electrolyte with a lithium salt concentration of 1 mol / L.
[0143]
Preparation of the positive electrode plate
[0144] Mix the positive electrode active material lithium cobalt oxide (LCO), conductive carbon black (Super P), and binder polyvinylidene fluoride (PVDF) in a weight ratio of 90:7:3. Add an appropriate amount of solvent N-methylpyrrolidone (NMP) and stir evenly to obtain the positive electrode slurry. Coat the positive electrode slurry on both surfaces of the aluminum foil and dry it in a vacuum oven at 100 °C for 12 hours. The positive electrode plate is obtained. The coating amount per unit area of the positive electrode active material on the positive electrode plate is 19.61 mg / cm 2 .
[0145]
Preparation of the lithium-ion battery
[0146] Use the negative electrode sheet and the positive electrode sheet prepared as described above; use a PE porous polymer film as the separator. Stack the positive electrode sheet, the separator, and the negative electrode sheet in sequence, with the separator in the middle of the positive and negative electrodes to play a separating role, and wind to obtain a bare battery cell. Place the bare battery cell in an outer package, inject the electrolyte prepared as described above, and then perform encapsulation. After processes such as formation, degassing, and edge trimming, a lithium-ion battery is obtained.
[0147] Example 2-15
[0148] The differences from Example 1 are as follows: For the parameters of the silicon-carbon material and the negative electrode sheet, see Table 2 for details.
[0149] Comparative Example 1-3
[0150] The differences from Example 1 are as follows: The preparation of the negative electrode sheet. Specifically:
[0151] Mix graphite with polyvinylidene fluoride and sodium carboxymethyl cellulose to prepare a first slurry; by mass percentage, graphite: polyvinylidene fluoride: sodium carboxymethyl cellulose is 97%: 2.4%: 0.6%.
[0152] Mix the silicon-carbon material with polyacrylate, carbon nanotubes, and sodium carboxymethyl cellulose to prepare a second slurry; by mass percentage, silicon-carbon material: graphite: polyacrylate: carbon nanotubes: sodium carboxymethyl cellulose is 20.0%: 74.0%: 5%: 0.5%: 0.5%. The specific performance parameters of the silicon-carbon material are shown in Table 2.
[0153] Coat the first slurry and the second slurry onto the current collector respectively, with the first film layer at the bottom and the second film layer on top.
[0154] Coat a mixed slurry of 6.5 mg / cm 2 on both surfaces of a 6-μm-thick copper foil and dry it. Cold press to a compaction density of 1.74 g / cm 3 . The negative electrode sheet is obtained.
[0155] For the parameters of Comparative Example 1 - Comparative Example 3, see Table 2 for details.
[0156] Comparative Example 4
[0157] The differences from Example 1 are as follows: The preparation of the negative electrode sheet. Specifically:
[0158] Mix graphite with polyvinylidene fluoride and sodium carboxymethyl cellulose to prepare a first film layer slurry; by mass percentage, graphite: polyvinylidene fluoride: sodium carboxymethyl cellulose is 97%: 2.4%: 0.6%.
[0159] Mix silicon-carbon material, graphite, polyacrylic acid, carbon nanotubes, and sodium carboxymethyl cellulose to obtain the slurry for the second film layer; by mass percentage, the silicon-carbon material: graphite: polyacrylate: carbon nanotubes: sodium carboxymethyl cellulose is 20.0%: 74.0%: 5%: 0.5%: 0.5%. The specific performance parameters of the silicon-carbon material are shown in Table 2.
[0160] Coat 4.5 mg / cm 2 of the slurry for the first film layer on both surfaces of a 6-μm-thick copper foil. After drying, coat 1.6 mg / cm 2 of the slurry for the second film layer on the first film layer and then dry. Cold press to a compaction density of 1.74 g / cm 3 ; thus obtaining the negative electrode sheet.
[0161] See Table 2 for the details of each parameter.
[0162]
Performance Test
[0163] 1. Performance Test of Negative Electrode Sheet
[0164] (1) Discharge the freshly prepared lithium-ion batteries of each example or comparative example to 3.0 V, disassemble to obtain the positive and negative electrode sheets, soak them in DMC (dimethyl carbonate) solution for 15 min and then dry for standby;
[0165] (2) Take the negative electrode sheet in (1), distinguish the first film layer and the second film layer through SEM (scanning electron microscopy) of the electrode sheet cross-section + element distribution, measure the thickness S2 of the second film layer of the single-sided electrode sheet, and conduct a nanoindentation test using the negative electrode sheet. Use a nanoindentation instrument with the equipment model Hysitron TI 990 TriboIndenter, with a probe pressing speed of 1 μm / second, apply a load until the displacement reaches S2, where S2 is less than or equal to the thickness of the second coating; release the load, monitor the recovery displacement S1, and calculate the recoverable displacement using S1 / S2.
[0166] Refer to Figure 2 and Table 1, Figure 2 Exemplarily shows the nanoindentation test relationship diagram; the specific data are shown in Table 1.
[0167] Table 1 Deformation amount (%) Compression Stress (Mpa) Rebound Stress (Mpa) 0 0 10 0.5 0 20 0.7 0.01 30 0.8 0.04 40 0.85 0.11 50 0.9 0.2 60 0.94 0.31 70 0.99 0.45 80 1.03 0.6 90 1.07 0.8 100 1.1 1.1
[0169] (3) Take the negative electrode sheet in (1) and measure the ash content after calcination, deduct the current collector, and convert to obtain the comprehensive Si element content (the comprehensive Si element content W2 in Table 2).
[0170] (4) Distinguish the thickness ratio of the first film layer and the second film layer (characteristic element Si) through the cross-sectional SEM + element distribution of the electrode in (1), and the mass percentage of Si element in the second film layer (upper layer) can be deduced from the comprehensive Si element content in (3) (the Si element content W1 in the second film layer in Table 2).
[0171] The test results of each example and comparative example are shown in Table 2.
[0172] 2. Performance test of lithium-ion battery
[0173] (1) Battery swelling rate during 2C / 0.5C cycling for 500 cycles
[0174] Measure the thickness of the fresh lithium-ion battery prepared in each example or comparative example as H0.
[0175] At 25°C, charge at a constant current of 2C to 4.5V, then charge at a constant voltage of 4.5V to 0.02C, let it stand for 5 minutes, and then discharge at 0.5C to 3.0V. This is one charge-discharge cycle process; then, cycle 500 times according to the above cycle process. At this time, the thickness of the lithium-ion battery is H1. The swelling rate after 500 cycles = (H1 - H0) / H0 × 100%.
[0176] The thickness test method is measured by a parallel flat plate with a pressure of 600g.
[0177] The test results of each example and comparative example are shown in Table 2.
[0178] (2) Energy density
[0179] Energy density = discharge capacity * discharge platform / battery volume.
[0180] The discharge capacity and discharge platform are measured by the following method: Charge the battery to the rated full charge voltage, and then discharge it to 3.0V at 0.2C, denoted as C1. Then charge it to the rated full charge voltage at a current of 0.2C1, and then discharge it to 3.0V.
[0181] The volume of the battery can be measured by measuring the battery thickness, battery length, and battery width through the general size measurement method in the battery field and then calculated.
[0182] The test results of each example and comparative example are shown in Table 2.
[0183] Table 2
[0184] It can be seen from the above table that:
[0185] Compared with other embodiments, in Example 10, it can be seen that controlling the mass percentage content W1 of Si element in the second film layer to satisfy 10% ≤ W1 ≤ 25%, and the second film layer binder and its content of 2% - 12% can further improve the recoverable displacement.
[0186] Compared with Comparative Example 1, Comparative Examples 3 - 4, Examples 1 - 4, Examples 8 - 9, it can be seen that on the premise that the comprehensive Si material content and the comprehensive Si element content W2 are the same:
[0187] The lithium - ion batteries prepared in Examples 1 - 4, Examples 8 - 9 effectively reduce the swelling rate during the battery cycle, and the energy density of Examples 1 - 4, Examples 8 - 9 is equivalent to that of each of the above - mentioned comparative examples.
[0188] Thus, it can be shown that the lithium - ion batteries prepared in Examples 1 - 4, Examples 8 - 9 can take into account the energy density of the battery while reducing the swelling during the battery cycle. Further, compared with Comparative Example 2, Examples 5 - 7, Examples 11 - 15, it can be seen that on the premise that the comprehensive Si material content and the comprehensive Si element content W2 are the same:
[0189] The lithium - ion batteries prepared in Examples 5 - 7, Examples 11 - 15 effectively reduce the swelling rate during the battery cycle, and the energy density of Examples 5 - 7, Examples 11 - 15 is equivalent to that of each of the above - mentioned comparative examples.
[0190] Thus, it can be shown that the lithium - ion batteries prepared in Examples 5 - 7, Examples 11 - 15 can take into account the energy density of the battery while reducing the swelling during the battery cycle.
[0191] In summary, the solution of the embodiments of the present application can take into account not reducing the energy density of the battery while reducing the swelling during the battery cycle.
[0192] The above - described embodiments are some embodiments of the present application, not all embodiments. The detailed description of the embodiments of the present application is not intended to limit the scope of the present application claimed, but merely represents selected embodiments of the present application. All other embodiments obtained by those of ordinary skill in the art based on the embodiments in the present application without making creative efforts fall within the scope of protection of the present application.
Claims
1. A negative electrode plate, characterized in that: The negative electrode plate comprises: Anode current collector; A first film layer, the first film layer comprising a first negative electrode active material, the first negative electrode active material being graphite; and a second film layer; the second film layer comprises a second negative electrode active material, the second negative electrode active material comprises a silicon-carbon material; relative to the second film layer, the first film layer is close to the surface of the negative electrode current collector; The nano-indentation test of the second film layer satisfies that the recoverable displacement is 60% to 100%.
2. The negative electrode sheet according to claim 1, characterized in that: The recoverable displacement is 80% to 100%.
3. The negative electrode sheet according to claim 1, characterized in that: Measured by mass percentage of the second film layer, the mass percentage content of Si element in the second film layer is W1; 10%≤W1≤25%; The second film layer includes: a binder; the binder includes: at least one of polyurethane, polyimide, and polyamide-imide; based on the mass percentage of the second film layer, the second film layer includes: 2% to 12% of the binder.
4. The negative electrode sheet according to claim 3, characterized in that: Measured by mass percentage of the second film layer, the mass percentage content of Si element in the second film layer is W1; 15%≤W1≤25%; the second film layer includes: 6% to 10% of the binder.
5. The negative electrode sheet according to any one of claims 1 to 3, characterized in that: The ratio of the coating weight of the second film layer to the coating weight of the first film layer is 0.10 to 0.
50.
6. The negative electrode sheet according to any one of claims 1 to 3, characterized in that: The ratio of the coating weight of the second film layer to the coating weight of the first film layer is 0.10 to 0.
20.
7. The negative electrode sheet according to any one of claims 1 to 3, characterized in that: The Dn10 of the silicon-carbon material is 3.7 μm to 5.0 μm.
8. The negative electrode sheet according to any one of claims 1 to 3, characterized in that: The Dn10 of the silicon-carbon material is 3.7 μm to 4.0 μm.
9. The negative electrode sheet according to any one of claims 1 to 3, characterized in that: The Dv10 of the silicon-carbon material is 5.1 μm to 6.1 μm.
10. The negative electrode sheet according to any one of claims 1 to 3, characterized in that: The Dv50 of the silicon-carbon material is 8.3 μm to 10.3 μm.
11. The negative electrode sheet according to any one of claims 1 to 3, characterized in that: The silicon-carbon material satisfies at least one of the following characteristics: (1) The Dv90 of the silicon-carbon material is 13.5 μm to 16.5 μm; (2) The Dv99 of the silicon-carbon material is less than or equal to 25.0 μm; (3) The specific surface area of the silicon-carbon material is 1.00 m2 / g to 3.50 m2 / g; (4) The tap density of the silicon-carbon material is 0.85 g / cm3 to 1.05 g / cm3.
12. An electrochemical device, characterized in that: The electrochemical device comprises: the negative electrode sheet according to any one of claims 1-11.
13. An electronic device, characterized in that: The electronic device comprises the electrochemical device according to claim 12.